Immune Response: A Missed Opportunity Between Vitamin D and Radiotherapy - Yu, Xinyue; Liu, Baocai; Zhang, Ning; Wang, Qian; Cheng, Guanghui (Frontiers in Cell and Developmental Biology, 2021)
Radiotherapy (RT) is a mainstay treatment in several types of cancer and acts by mediating various forms of cancer cell death, although it is still a large challenge to enhance therapy efficacy. Radiation resistance represents the main cause of cancer progression, therefore, overcoming treatment resistance is now the greatest challenge for clinicians. Increasing evidence indicates that immune response plays a role in reprogramming the radiation-induced tumor microenvironment (TME). Intriguingly, radiation-induced immunosuppression possibly overwhelms the ability of immune system to ablate tumor cells. This induces an immune equilibrium, which, we hypothesize, is an opportunity for radiosensitizers to make actions. Vitamin D has been reported to act in synergistic with RT by potentiating antiproliferative effect induced by therapeutics. Additionally, vitamin D can also regulate the TME and may even lead to immunostimulation by blocking immunosuppression following radiation. Previous reviews have focused on vitamin D metabolism and epidemiological trials, however, the synergistic effect of vitamin D and existing therapies remains unknown. This review summarizes vitamin D mediated radiosensitization, radiation immunity, and vitamin D-regulated TME, which may contribute to more successful vitamin D-adjuvant radiotherapy.